Primary Squamous Cell Carcinoma of the Rectum: a Case Report - O, Faidzal; MN, Azmi; R, Kalavathi (IIUM Medical Journal Malaysia, 2013)
Squamous cell carcinoma of the rectum is a very rare malignancy. In the literature, the incidence has been reported as 0.25 to 0.1 per 10000 colorectal carcinomas. Due to its rarity, the treatment and behavior of this tumor have only been discussed in case reports. As a result, several theories regarding their pathogenesis have been proposed. We will describe our experience in managing this rare malignancy in a 69-year-old man who presented with altered bowel habit. Surgery remains the mainstay of treatment. Issues regarding additional treatment have been presented in the literature. The rarity of this tumour also raises issues regarding criteria for diagnosis which we will try to highlight and discuss.